Pengujian Hubungan Simultanitas Antara Kepemilikan Manajerial Dan Kebijakan Hutang (Studi Empiris pada Bursa Efek Indonesia) - Shaffira, Fernanda Sheila; Sunarjanto, N. Agus; Sina, Siprianus S. (Kajian Ilmiah Mahasiswa Manajemen, 2017)
The purpose of this study was to examine the relationship between managerial ownership and debt policy. Based on nonlinear simultaneous equations in Indonesian firms listed on the Indonesian stock exchanges during the 2011-2016 research period, this study shows that managerial ownership and debt policy have simultaneous relationships. By using Simultaneous Equation Model, the research result shows that debt policy has a positive effect on managerial ownership. In addition, this study proves that managerial ownership has a nonmonotonic relationship to debt policy. When managerial ownership under 7,8% has a positive relationship to debt policy. Then, when managerial ownership is in the range of 7,8% to 24% will be negatively related. However, when managerial ownership above 24% it will positively affect. The results of this study proves that managers in the company can behave entrench or alignment in making decisions about managerial ownership and debt policy.